Biomass, growth and ecophysiological responses of young plants of bertholletia excelsa bonpl. Subjected to different levels of irradiance - Carmo Ribeiro de Souza, Cristiane Santos do; Santos, Victor Alexandre Hardt Ferreira dos; Ferreira, Marciel José; Gonçalves, José Francisco de Carvalho (Ciência Florestal, 2017)
Brazil nut (Bertholletia excelsa Bonpl.) is a light-demanding species, because in natural forest, the species depending of formation of clearings for reach reproduction size and in forest plantation, showing fast initial growth when exposed to high levels of irradiance. However, the ecophysiological traits of this species under contrasting conditions of irradiance were not investigated. In this study, in addition to growth traits, we investigated for first time the degree of plasticity of ecophysiological response of Bertholletia excelsa when subjected to contrasting irradiance environments. Young plants of Bertholletia excelsa were cultivated under three conditions of irradiance: low (20-300 μmol m-2 s-1), moderate (800-1000 μmol m-2 s-1) and high (1900-2100 μmol m-2 s-1). We analyzed the growth traits, gas exchange, chloroplastid pigment contents and, the end of experiment, the accumulation and partitioning of biomass. Young plants of Bertholletia excelsa showed the highest values of biomass, growth and photosynthesis when exposed to environments of moderate and high irradiance. Low irradiance condition stimulated more biomass partitioning for shoot and chloroplastid pigment contents. Bertholletia excelsa showed physiological plasticity under contrasting conditions of irradiance, the largest growth and biomass accumulation in environments of moderate and high irradiance were promoted by better photosynthetic performance, whereas the positive carbon balance under low irradiance is ensured by investment in structures of interception and energy harvesting. © 2017 Ciência Florestal, Santa Maria, All right reserved.
Biomassa, crescimento e respostas ecofisiológicas de plantas jovens de bertholletia excelsa bonpl. Submetidas a diferentes níveis de irradiância